Biological perspectives in geotechnics: Application and monitoring - Mishra, Partha Narayan; Jain, Surabhi; Bore, Thierry; Chang, Ilhan; Kwon, Yeong Man; Wang, Yijie; Dash, Hirak Ranjan; Kumar, Ashutosh; Tiwari, Satyam; Jiang, Ningjun; Das, Sarat Kumar; Scheuermann, Alexander (Journal of Rock Mechanics and Geotechnical Engineering, 2024)
This paper builds on exploring the applications of biomediated pathways to solve geotechnical challenges. First, the state of the art of biological remediation strategies including microbial remediation and phytoremediation have been introduced and critically reviewed in the context of decontaminating the soils. Next, biopolymerisation, biomineralisation and bioneutralisation processes have been depicted with a special emphasis on the applications including but not limited to soil stabilisation, soil erosion prevention, anti-desertification and pH neutralisation. Each of these methods have their own limitations and bottlenecks while scaling up, and these challenges have been summarised and some possible paths to overcome the challenges have also been discussed. The state of the art of electromagnetic (EM) monitoring methods to capture the effects of biomediation on spatio-temporal soil properties are then highlighted as a non-invasive and rapid pathway to track the progress of biomediated soil processes. Finally, each of the technologies discussed have been evaluated for their maturity level using the principles of technology readiness level (TRL). A majority of the technologies amounting to around 77% are still in the TRL 4–7, i.e. in the valley of death. It is thus evident that development of these technologies needs to be supported with appropriate funding for improving their maturity to a level of industrial deployment.
Keywords: Biogeotechnics; Biomineralisation; Biopolymers; Bioremediation; Electromagnetic (EM) methods technology readiness level (TRL); Phytoremediation